Pendampingan Tertib Administrasi Keuangan Demi Peningkatan Kinerja Keuangan UMKM Pengolahan Snack di Padukuhan Mertosanan Kulon - Puteri Oktatia Harum; Ratri Paramitalaksmi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Limited understanding of the preparation of financial reports is something that is often experienced by MSMEs that have just been established. This Community Service Activity aims to support MSME players, nameli MSMEs in the Mertosanan Kulon, Potorono, Banguntapan Bantul areas where the majority of the population is snack entrepreneurs to increase income by sharing knowlage through assistance related to recording financial transactions and preparing financial reports related to online marketing. From this assistance, it is hoped that it can help MSME actors to compete in the market. The methods used in this service are: 1) Socialization and Coordination. 2) Data Collection. 3) Implementation of Mentoring. 4) Implementation of Training. The result of the service carried out show that the service that has been carried out has increased their skills in developing businesses for MSME actors.